Korelasi indeks sefalik dan gigi berjejal rahang atas pada anak umur 7-12 tahun - Shung, Wong Weng; Primarti, Risti Saptarini; Latif, Deni Sumantri (Fakultas Kedokteran Gigi Universitas Padjadjaran, 2017)
Pendahuluan: Prediksi awal risiko gigi berjejal rahang atas berguna untuk kedokteran gigi estetika dan perawatan ortodontik yang efektif. Tujuan penelitian ini adalah untuk mengetahui apakah indeks sefalik berkorelasi dengan kondisi gigi berjejal rahang atas anak pada periode gigi geligi campuran. Metode: Metode penelitian ini adalah studi Cross sectional. Populasi penelitian merupakan pasien anak yang datang ke Departemen Kedokteran Gigi Anak pada periode bulan November 2016. Teknik sampling menggunakan teknik purposive sampling dan didapatkan subjek lima puluh anak. Indeks sefalik diukur dengan menggunakan spreading caliper, sementara gigi rahang atas berjejal dinilai dengan mencocokkan foto oklusi yang sesuai dengan standardized foto dari IOTN. Data ditabulasi dan dianalisis dengan Uji korelasi Spearman. Hasil: Hasil penelitian menunjukkan bahwa terdapat hubungan indeks sefalik dengan gigi berjejal rahang atas dengan nilai rs = -0.68. p-value adalah <0.05 Simpulan: Terdapat korelasi yang signifikan antara indeks sefalik dan gigi berjejal rahang atas pada anak umur 7-12 tahun.Â Correlation between cephalic index and anterior maxillary crowding of 7-12-years-old childrenÂ ABSTRACTIntroduction: Early prediction of the potential risk in maxillary dental crowding can be useful for the practice of aesthetic dentistry as well as for effective orthodontic treatment. The purpose of this research is to examine whether the cephalic index can be a method in prediction of maxillary dental crowding of mixed-dentition stage children. Methods: The type of this research method is a cross sectional study. The population of this research is determined by periodic interval sampling in which the patients who came to RSGM in the month of November. Technique sampling used for this research is purposive sampling and fifty subjects were selected. Cephalic index was measured by using a spreading caliper, while maxillary dental crowding was assessed by matching photograph occlusal to the nearest resemblance on standardized photographs of IOTN. Data tabulation and analysis with Spearmanâs correlation test. Results: The results showed that there is relationship between cephalic index and maxillary dental crowding with rs = -0.68. As a conclusion, the p-value < 0.05. Conclusion: There is significant correlation betwen cephalic index and maxillary dental crowding of 7-12 years old children.Keywords: Cephalic index, maxillary dental crowding, IOTN.